STUDI AWAL REKAYASA PROSES PRODUKSI TEH HIJAU BERKATEKIN TINGGI MELALUI TEKNOLOGI STEAMING - Yulianto, Mohammad Endy; Senen, Senen; Ariwibowo, Didik (METANA, 2007)
Abstract Tea is a nalural healty, beverage because of catechin content which is a bioactive matter that can retard cancel growth, heart desease, blood and nerves, making healthy for mouth, teeth and some other infection. Therefore, high catechin in tea would be needed. To Obtain high catechin contend it must eliminate enzymatically oxidation process of polyphenol during tea manufacturing. Thus, it was created a process and processing system which sustain the process. The basic design was inactivation of polyphenol oxidase enzyme by steaming. It wishes a high catechin green tea product that can either be directly as a beverage or as a catechin powder for dietary food and functional food or medicine. The variables of this study, were percentage of steam, tea leaves feeding and humidity. The investigated parameters were temperature, catechin content, moisture content, and humidity as time function. The result was that at 900C yielded high catechin. The study shows that at 70% humidity yielded higher catechin and lower moisture content. Keywords : Green tea; Steaming